Term structure of interest rate and macro economy: An empirical study on selected emerging countries sovereign bond - Mochammad Doddy Ariefianto; Citra Amanda; Zaäfri Ananto Husodo (Journal of Capital Markets Studies (JCMS), 2024)
Purpose - To examine the relationship between the term structure of interest rates of sovereign bonds in emerging nations and their macroeconomic indicators, specifically emphasizing its persistence and interaction with inflation, foreign exchange and fiscal conditions. Design/methodology/approach - Adopting the Mean Group Instrumental Variables (MGIV) technique, as proposed by Cui et al. (2020) and Norkute et al. (2021), this study analyzes a monthly panel dataset from nine emerging economies spanning January 2010 to October 2021, totaling 1,278 observations. Findings - The findings reveal significant persistence in both slope and curvature, with a rising yield level linked to the term structure's flattening, while shifts in inflation and exchange rates correlate with its steepening. Originality/value - Our study is among the few which used an empirically constructed measure of the term structure of interest instead of a theoretical construct. To best our knowledge, we are the first to employ MGIV.
Keywords: C23; E43; E44; E52; F31; G12; 330; Curvature; Financial stability; Mean group instrumental variables; Panel econometric; Slope; Term structure of interest